Zinc(II) phthalocyanines immobilized in mesoporous silica Al-MCM-41 and their applications in photocatalytic degradation of pesticides - Silva, M. (2012)
In the present study the authors investigated a set of three new zinc(II) phthalocyanines (zinc(II) tetranitrophthalocyanine (ZnTNPc), zinc(II) tetra(phenyloxy)phthalocyanine (ZnTPhOPc) and the tetraiodide salt of zinc(II)tetra(N,N,N-trimethylaminoethyloxy) phthalocyaninate (ZnTTMAEOPcI)) immobilized into Al-MCM-41 prepared via ship-in-a-bottle methodology. The samples were fully characterized by diffuse reflectance-UV–vis spectroscopy (DRS-UV–vis), luminescence, thermogravimetric analysis (TG/DSC), N2 adsorption techniques and elemental analysis. A comparative study was made on the photocatalytic performance upon irradiation within the wavelength range 320–460 nm of these three systems in the degradation of pesticides fenamiphos and pentachlorophenol. ZnTNPc@Al-MCM-41 and ZnTTMAEOPcI@Al-MCM-41 were found to be the most active systems, with the best performance observed with the immobilized cationic phthalocyanine, ZnTTMAEOPcI@Al-MCM-41. This system showed high activity even after three photocatalytic cycles. LC–MS product characterization and mechanistic studies indicate that singlet oxygen (1O2), produced by excitation of these immobilized photosensitizers, is a key intermediate in the photocatalytic degradation of both pesticides.